2021
DOI: 10.1155/2021/9978206
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomogram Based on Circular RNA‐Associated Competing Endogenous RNA Network for Patients with Lung Adenocarcinoma

Abstract: Evidence is increasingly indicating that circular RNAs (circRNAs) are closely involved in tumorigenesis and cancer progression. However, the function and application of circRNAs in lung adenocarcinoma (LUAD) are still unknown. In this study, we constructed a circRNA-associated competitive endogenous RNA (ceRNA) network to investigate the regulatory mechanism of LUAD procession and further constructed a prognostic signature to predict overall survival for LUAD patients. Differentially expressed circRNAs (DEcirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“… Kim et al, 2019 ; Z. Li Y. et al, 2021 ; Perdrizet et al, 2021 ; Provencio et al, 2021 ; Yamaguchi et al, 2021 ). Erlotinib, the first approved target drug for NSCLC, is a reversible tyrosine kinase inhibitor that targets the epidermal growth factor receptor and can significantly improve the survival of LUAD patients ( Faehling et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Kim et al, 2019 ; Z. Li Y. et al, 2021 ; Perdrizet et al, 2021 ; Provencio et al, 2021 ; Yamaguchi et al, 2021 ). Erlotinib, the first approved target drug for NSCLC, is a reversible tyrosine kinase inhibitor that targets the epidermal growth factor receptor and can significantly improve the survival of LUAD patients ( Faehling et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further Pearson correlation was carried out to analyze the correlation between hsa_circ_0086354 and miRNAs, only interactions with significant negative correlation was retained. The circRNAs-miRNAs network was visualized by Cytoscape software (version 3.7.0; http://www.cytoscape.org ) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] Recently, new evidence has shown that circRNAs participate in the initiation and development of LUAD. [10][11][12] Through bioinformatic analysis and literature reviews, [13][14][15] the consistent upregulation of circ 0072088 expression in LUAD has persuaded us to further examine its role. Paradoxically, some reports have shown that the downregulation of circ 0072088 in hepatic carcinoma cells derived exosome is associated with tumorigenesis, 16 similarly, its decrease has been reported to be associated with metastasis of colorectal cancer, 17 suggesting that, it is necessary to further explore the expression and function of circ 0072088 in the mechanisms underlying LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that circRNAs, which mainly function as molecular sponge by absorbing microRNAs and affecting gene expression, are involved in tumorigenesis and deterioration 7–9 . Recently, new evidence has shown that circRNAs participate in the initiation and development of LUAD 10–12 . Through bioinformatic analysis and literature reviews, 13–15 the consistent upregulation of circ 0072088 expression in LUAD has persuaded us to further examine its role.…”
Section: Introductionmentioning
confidence: 99%